Tics, OCD and ADHD Associated with Brain Tumor - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers at Children's Hospital of Michigan, Detroit report a boy aged 12 years with a 12-month history of ADHD, OCD, and stimulant-induced tourette syndrome that resolved following surgical removal of a right temporal lobe and basal ganglia oligodendroglioma.